UNLIKELY INTERSECTIONS IN FINITE CHARACTERISTIC. (9th August 2018) - SHANKAR, ANANTH N.; TSIMERMAN, JACOB
Abstract : We present a heuristic argument based on Honda–Tate theory against many conjectures in 'unlikely intersections' over the algebraic closure of a finite field; notably, we conjecture that every abelian variety of dimension 4 is isogenous to a Jacobian. Using methods of additive combinatorics, we answer a related question of Chai and Oort where the ambient Shimura variety is a power of the modular curve.